Effect of various alkaline agents on the size and morphology of nano-sized HKUST-1 for CO2 adsorption1. Issue 35 (18th April 2015) - Xin, Chunling; Zhan, Haijuan; Huang, Xin; Li, Hongguang; Zhao, Ning; Xiao, Fukui; Wei, Wei; Sun, Yuhan
<x xml:space="preserve">Abstract</x> Two type of modulators, including sodium acetate and triethylamine were used to synthesize nanosized HKUST-1 crystals with tailored size and morphology using a coordination modulation method.